Centralized HIV Program Oversight: An Investigation of a Case Series of New HIV Infections among US Army Soldiers, 2012 to 2013. Issue 46 (November 2015) - Pacha, Laura A.; Hakre, Shilpa; Myles, Otha; Sanders-Buell, Eric E.; Scoville, Stephanie L.; Kijak, Gustavo H.; Price, Michael W.; Mody, Rupal M.; Liu, Ying; Miller, Shana L.; Pham, Phuc T.; Michael, Nelson L.; et al.
Abstract : Abstract: Centralized HIV program oversight and repeal of the Department of Defense policy "Don't Ask Don't Tell" permitted characterization of HIV transmission among soldiers assigned to a large US Army base in the continental United States from 2012 to 2013. An investigation of a greater than expected number of new HIV infections among soldiers was initiated to characterize transmission and identify opportunities to disrupt transmission and deliver services. All soldiers who were assigned to the base at the time of their first positive HIV test and who had their first positive HIV test in 2012 or in the first 6 months of 2013 and who had a clinical genotype available for analysis were eligible for inclusion in the investigation. All patients (n = 19) were men; most were black (52%) and less than 30 years old (64%). Fifteen of the 19 patients participated in in-depth interviews. Eighty percent were men who have sex with men who reported multiple sex partners having met through social and electronic networks. All were subtype B infections. Significant knowledge gaps and barriers to accessing testing and care in the military healthcare system were identified. Most (58%) belonged to transmission networks involving other soldiers. This investigation represents an important step forward in on-going efforts to develop a comprehensive understanding of transmission networks in the Army that can inform delivery of best practices combination prevention services. The Army is developing plans to directly engage individuals in key affected populations most at risk for HIV infection to identify and address unmet needs and expand delivery and uptake of prevention services. Further investigation is underway and will determine whether these findings are generalizable to the Army.